Energy analysis of building N°1 of the Technological University of Panama: simulation and optimization of electrical energy consumption through energy efficiency solutions - Gollini-Mihalopoulos, Constantino (2022)
In 2017, the International Energy Agency estimated that 40% of the reduction in pollutant gas emissions needed to limit the global temperature increase to two degrees by 2050 could be achieved from energy efficiency measures. In this research, the annual electricity consumption of building N°1 of UTP was evaluated by software, the result was compared with the most recent billing available and energy efficiency measures were proposed, whose economic and environmental benefits were also studied. Among the recommended proposals are the installation of LED lamps, photovoltaic generation, adaptations to the air conditioning system, efficient windows, and ventilation of the attic of the roof of building N°1, together with the installation of radiant barriers. The results obtained show a consumption of 2 497 912 kWh / year, which would be reduced by 38.81%, representing a saving of B /. 218 426.14 per year and a decrease of 57.27% in CO2 emissions.